Experimental research on flow development and control effectiveness in the duct at high speed - Khan, Sher Afghan; Ahmad, Zaheer; Aabid, Abdul; Mokashi, Imran (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper presents an experimental study of suddenly expanded flows at supersonic speed is performed. A Convergent-divergent (C-D) nozzle is used with suddenly expanded duct. At the recirculation zone, the pressure is controlled by using four microjets of 1 mm diameter arranged at PCD of 1.3 as an active control mechanism to regulate the pressure in the wake region. The development and the quality of the flow were monitored to ensure that the flow control does not aggravate the flow field in the duct. The geometrical and the inertia parameters are the area ratio and the Mach number. The area of the study was 3.24, L/D ratio was from 10 to 1, and the level of inertia as 2.1. The expansion level considered during the experiments was from 3 to 11. The results clearly indicate that the wall pressure variation with and without control in the enlarged duct does not vary, which means that the use of control does not affect the flow filed in the circular duct.